2022
DOI: 10.3390/nano12091606
|View full text |Cite
|
Sign up to set email alerts
|

Microorganism-Templated Nanoarchitectonics of Hollow TiO2-SiO2 Microspheres with Enhanced Photocatalytic Activity for Degradation of Methyl Orange

Abstract: In this study, hollow SiO2 microspheres were synthesized by the hydrolysis of tetraethyl orthosilicate (TEOS) according to the Stober process, in which Pichia pastoris GS 115 cells were served as biological templates. The influence of the preprocessing method, the TEOS concentration, the ratio of water to ethanol, and the aging time on the morphology of microspheres was investigated and the optimal conditions were identified. Based on this, TiO2-SiO2 microspheres were prepared by the hydrothermal process. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Physicochemical properties of the TiO S3. Comparative study of the photocatalytic activity with different TiO 2 /SiO 2 photocatalysts [59][60][61][62][63][64][65][66].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Physicochemical properties of the TiO S3. Comparative study of the photocatalytic activity with different TiO 2 /SiO 2 photocatalysts [59][60][61][62][63][64][65][66].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Numerous studies have reported the synthesis of SiO 2 /TiO 2 core/shell materials with desirable properties in terms of the specific surface area, pore volume, hydrophilicity, and toxicity [ 15 , 16 , 17 ]. SiO 2 /TiO 2 core/shell materials are employed in numerous applications, including as light-scattering materials for dye-sensitized solar cells, nanocarriers for drug delivery, and photocatalysts [ 18 , 19 , 20 , 21 , 22 , 23 ]. Furthermore, the properties of the outermost TiO 2 shell can be manipulated through various surface treatments [ 24 ].…”
Section: Introductionmentioning
confidence: 99%